Draft genome sequence of a human-associated isolate of Haloferax alexandrinus strain Arc-hr, an extremely halophilic archaea. (January 2017) - Khelaifia, S.; Caputo, A.; Djossou, F.; Raoult, D.
Abstract: We report the draft genome sequence of Haloferax alexandrinus strain Arc-hr (CSUR P798), isolated from the human gut of a 10-year-old Amazonian individual. Its 3 893 626 bp genome exhibits a 66.00% GC content. The genome of the strain Arc-hr contains 37 genes identified as ORFans, seven genes associated to halocin and 11 genes associated with polyketide synthases or nonribosomal peptide synthetases.